Keterkaitan New HSK dan Kurikulum Bahasa Mandarin di Perguruan Tinggi - Budianto, Pauw; Laurencia, Noviana (Lingua Cultura, 2014)
This research is to find out the correlation between the New HSK (Hanyu Shuiping Kaoshi)/International Mandarin Proficiency Test and the Mandarin Skill Curriculum in higher education in Indonesia, with case study at Chinese Department of Maranatha Christian University Bandung. Methods used in this research are survey and literature studies, with quantitative and qualitative analytic description. The results show that New HSK could be used as achievement tests for students of Chinese Department at each level of study. Besides, New HSK could also be one of measurement tools for curriculum needs analysis, which means that the change of students’ achievements in New HSK would decide the adjustments of the Mandarin skill curriculum at whole.